Concepts and terms for dose/volume parameters in carbon-ion radiotherapy: Conclusions of the ULICE taskforce Concepts et terminologie des paramètres de dose et volumes proposés en hadronthérapie par ions carbone - Vogin, Guillaume; Wambersie, A.; Poetter, R.; Beuve, Michaël; Combs, S. E.; Magrin, Giulio; Mayer, R.; Mock, U.; Sarrut, David; Schreiner, T.; Fossati, P.; Balosso, J. (Cancer Radiotherapie, 2018)
Purpose: The Union of Light Ion Centers in Europe (ULICE) program addressed the need for uniting scientific results for carbon-ion radiation therapy obtained by several institutions worldwide in different fields of excellence, and translating them into a real benefit to the community. Particularly, the concepts for dose/volume parameters developed in photon radiotherapy cannot be extrapolated to high linear energy transfer particles. Methods and Materials: The ULICE-WP2 taskforce included radiation oncologists involved in carbon-ion radiation therapy and International Commission on Radiation Units and Measurements, radiation biologists, expert physicists in the fields of carbon-ion radiation therapy, microdosimetry, biological modeling and image-guided radiotherapy. Consensual reports emerged from multiple discussions within both the restricted group and the wider ULICE community. Public deliverables were produced and disseminated to the European Commission. Results: Here we highlight the disparity in practices between treating centers, then address the main topics to finally elaborate specific recommendations. Although it appears relatively simple to add geometrical margins around the clinical target volume to obtain the planning target volume as performed in photon radiotherapy, this procedure is not appropriate for carbon-ion radiation therapy. Due to the variation of the radiation quality in depth, there is no generic relative biological effectiveness value for carbon-ions outside of an isolated point, for a given fractionation and specific experimental conditions. Absorbed dose and “equieffective dose” for specified conditions must always be reported. Conclusions: This work contributed to the development of standard operating procedures for carbon-ion radiation therapy clinical trials. These procedures are now being applied, particularly in the first phase III international, multicenter trial (PHRC Étoile).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Carbon-ion radiotherapy; Clinical trials; Equieffective dose; Prescription; PTV; Recording; Specification